Generating multiple resilience dividends from managing unnatural disasters in Asia opportunities for measurement and policy - Reinhard Mechler; Stefan Hochrainer-Stigler (Asian Development Bank (ADB), 2019)
Despite solid evidence regarding the large benefits of reducing disaster risk, it has remained difficult to motivate sustained investment into disaster risk reduction (DRR). Recently, international policy debate has started to emphasize the need for focusing DRR investment toward actions that generate multiple dividends, including reducing loss of lives and livelihoods, unlocking development, and creating development cobenefits. We examine whether available and innovative decision support tools are fit-for-purpose. Focusing on the Asia region, we identify evidence of multiple dividends crafted using expert-based methods, such as cost-benefit analysis for selecting and evaluating "hardresilience- type" interventions. Given a rising demand for "softer" and systemic DRR investments in projects and programs, participatory decision support tools have become increasingly relevant. As one set of tools, resilience capacity (capital) measurement approaches may be used to support actions and decisions throughout all stages of the project cycle. Measuring capacity for resilience dividends, not outcome, such tools can serve as participatory decision support for organizations working at community and other levels for scoping out how development and disaster risk interact, as well as for supporting the cogeneration of multiple resilience dividend-type solutions with those at risk.
Keywords: O21; O22; Q56; 330; decision support; disaster risk; multiple dividends; resilience